Vocational High School Students’ Habits of Mind In Physics Material Through Discovery Learning Models - Heni Astatin; Tantri Mayasari; Farida Huriawati; Rinko Oi (STKIP Singkawang, 2020)
The Habits of Mind of SMK students must be classified as high, therefore researchers conducted research on investigating the thinking habits of SMK students by using the help of learning models based on problem solving in their own way (Discovery Learning). The method used is descriptive qualitative with a sample size of 33 students of class X in SMK Madiun. Data collection uses initial and final tests. The results of the study said that students' thinking habits improved after being given questions in the form of test training, and assisted with discovery learning models. Judging from the average number of pretest and posttest worth 80.8 and 115 the n-gain value is 0.6 with the medium category, the value is obtained from each indicator of habits of mind thinking about thinking 1 with high category, thinking flexibly 0.9 with high category, applying past knowledge to new situation 0.7 with high category, questioning and posing problem 0.6 with medium category, creating, imagining, innovating 0.2. Based on the N-gain value of each indicator, it can be concluded that the discovery learning model can improve students' habits of mind.